Estado de exceção e dispositivos: contribuições da filosofia de Giorgio Agamben à educação - Silva, Hanna Maria Ramos (2023)
This work aims to analyze certain concepts presente in some Works by Italian author Giorgio Agamben. Our analysis delas, above all, with the political and social fields. The concepts worked by both are very current and, therefore, opportune for our reflection, since they are necessary for the study of the political world. Thus, it is necessary to understand Agamben’s thought, which requires the articulation of concepts such as state of exception and bare life, that is, the state of abandonment in which individuals are deprived of political power in contemporary times; homo sacer(na excluded, disfigured or social outcast); biopolitics (which can take the formo f government devices, or the power of low), among others. It is also tolerant to bring the various surveillance practices used in various areas, such as social, cultural and, mainly, economic, in contemporary times, as such practices, in addition to using different technologies, discourses, institutions, policies, etc., they also result in power relations, or rather, in a surveillance policy, in which there is the production and proliferation of subjectivation processe. Therefore, state of exception, sovereignty, homo sacer, field and devices will be worked through the eyes of Agamben, with a view to potentiality, given the various means of capturing the contemporary subject.